Enhancing Financial Capability and Inclusion in Azerbaijan : A Demand-Side Assessment - World Bank Group (World Bank, Washington, DC, 2016)
Consumer protection is an important element of financial sector stabilization and development agenda in Azerbaijan. The falling oil prices and weaker macroeconomic fundamentals on top of the negative external shocks have led to devaluation of the national currency and erosion of public trust in financial sector. Restoring financial stability, renewing public and investor confidence and mobilizing higher savings to finance growth are the top priorities of Azerbaijan policy makers. The authorities increasingly discuss the issues of consumer and depositor protection, responsible lending and finance access. To support Azerbaijan in its efforts to advance financial capability, the WBG has implemented a nationally representative financial capability survey of the adult population in Azerbaijan. This survey will inform the development of a detailed implementation action plan for the national financial literacy strategy. Moreover, it will help the authorities to set quantifiable and concrete targets, and assess the effectiveness of future financial capability enhancing programs. Chapter 1 explores the financial inclusion landscape in Azerbaijan. Chapter 2 gives an overview of levels of financial capability in Azerbaijan, in particular about their financial knowledge, attitudes and behaviors. The last chapter investigates if the products are effectively meeting their needs of financially included individuals.